TUNAS BAMBU DALAM KARYA KERAMIK - Heruningrum, Heruningrum; Pratama, Randi; Kurniawan, Ramadhani (INSTITUT SENI INDONESIA PADANGPANJANG, 2023)
Bamboo shoots are plants that grow at the base of a bamboo clump filled with gluggut (bamboo hair) which when touched the body feels itchy. Bamboo shoots have a unique and varied shape, there are small, large, straight, curved, and others. The characteristic shape of bamboo shoots is that they are round and tapered (cone) so that this bamboo plant is very attractive as a work of art using ceramic media.The method of creating bamboo shoots in ceramics goes through three stages, namely the exploration stage is to find sources of reference data for writing books, journals, web and direct data in the field. The design stage is making pictures of ceramicworks into alternative sketches and selecting sketches to be used as designs for works of art, the embodiment stage is the process of embodiment of the work that has been designed into a work of art using Earthenware clay as the main ingredient,tools, techniques, both massage, slab , rotate, so as to produce work entitled always, useful, proud, my wish and my hope.